Endocannabinoid activation of CB1 receptors contributes to long‐lasting reversal of neuropathic pain by repetitive spinal cord stimulation. (20th January 2017) - Sun, L.; Tai, L.; Qiu, Q.; Mitchell, R.; Fleetwood‐Walker, S.; Joosten, E.A.; Cheung, C.W.
Abstract: Background: Spinal cord stimulation (SCS) has been shown to be effective in the management of certain neuropathic pain conditions, however, the underlying mechanisms are incompletely understood. In this study, we investigated repetitive SCS in a rodent neuropathic pain model, revealing long‐lasting and incremental attenuation of hyperalgesia and a mechanism of action involving endocannabinoids. Method: Animals were implanted with monopolar electrodes at the time of partial sciatic nerve injury. Dorsal columns at spinal segments T12/13 were stimulated 3 days later (early SCS), and again at day 7 (late SCS) using low‐frequency parameters. Hypersensitivity to cutaneous mechanical stimuli was assessed using von Frey filaments. Pharmacological agents, selected to identify endocannabinoid and opioid involvement, were administered intraperitoneally, 10 min before SCS. Results: Early SCS caused partial reversal of mechanical hypersensitivity with corresponding changes in the biomarker of central sensitization, [phospho‐Tyr 1472 ]‐GluN2B. The partial reversal of hyperalgesia by early SCS was amplified by co‐administration of LY 2183240, an inhibitor of endocannabinoid reuptake/breakdown. This amplification was inhibited by a CB1 R antagonist, AM251, but not by a CB2 R antagonist, AM630. Early SCS‐induced reversal of hyperalgesia was attenuated by naloxone, indicating a role for opioids. Late SCS resulted in an incremental level of reversal of hyperalgesia, which was inhibited by AM251, but not by CB2 or opioid receptor antagonists. Conclusion: The endocannabinoid system, and in particular the CB1 R, plays a pivotal role in the long‐lasting and incremental reversal of hyperalgesia induced by repetitive SCS in a neuropathic pain model. Significance: Alternative parameters for repetitive spinal cord stimulation (SCS) at 25/10 Hz elicit particularly long‐lasting and incremental reversal of hyperalgesia in a neuropathic pain model through a mechanism involving endocannabinoids.